Kebijakan Pengentasan Kemiskinan di Indonesia: Sebuah Fakta di Indonesia - A, Arliansyah; F, Fuadi; W, Wardhiah; Pasarela, Husni; Juanda, Reza (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze policies in poverty alleviation in Indonesia. The background of this study covers various aspects of policies implemented by the government in overcoming poverty. Although various programs and policies have been implemented, poverty in Indonesia is still a serious problem. This study uses a qualitative approach by collecting primary and secondary data. Secondary data is used as a reference from previous studies. While primary data is obtained through observations of government poverty alleviation policies. The discussion and analysis involve the concept of poverty, dimensions of poverty, and indicators of poverty. The results of this study are expected to provide a better understanding and insight into poverty alleviation policies in Indonesia and provide input for improving more effective policies.